Retratos da inclusão escolar a biopolítica em um caso ficcional - Amaral, Bruna Carla de Carvalho (Editora Oficina Universitária, 2022)
The paths taken in the teaching and learning processes inscribe marks on the subjects that cross them. It was the desire to explore some of these records that encouraged the master's research, now unfolded in this work, which sought to problematize school inclusion practices from a dialogue with biopolitics.